Sexisme en musique : des trucs pour s’assurer une programmation paritaire et inclusive – Partie 1 - Daguzan Bernier, Myriam (Gazette des femmes, 2019)
Chaque année, les festivals de musique pullulent. Qu’il soit à Montréal ou à Gaspé, à Trois-Rivières ou à Tadoussac, le public a l’embarras du choix pour voir les artistes qu’il préfère. Mais, alors que l’été amène son lot de têtes d’affiche, un redoutable ver d’oreille refait surface : où sont les femmes*? Solutions concrètes en deux temps pour améliorer leur présence dans les événements musicaux…
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; LGBTQIA2+; conciliation famille-travail; famille; femmes* artistes; identités LGBTQIA2+; inclusion; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques; travail

Feminist economics: Theoretical and political dimensions feminist economics - Agenjo-Calderón, Astrid; Gálvez-Muñoz, Lina (American Journal of Economics and Sociology, 2019)
Feminist economics is a school of economic thought and political action that gained important visibility during the 1990s, although its origins can be dated back to the mid-19th century. Since then, feminist economics has developed its own concepts, analytical frameworks, and methodologies. With gender as a central category, it seeks a more integral and humane comprehension of the economy and of the processes of inclusion and exclusion taking place in it. In addition, feminist economics has grown into a political practice that aims at improving the functioning of the economic system so that all people can have access to a dignified life on the basis of equality. This article presents a general systematization of these theoretical and political dimensions, particularly focusing on the critique of the neoclassical paradigm and its political correlates. We connect the epistemological, methodological, and conceptual contributions of feminist economics, as well as its propositions for transformative action, to specific debates on economic issues, such as the ecological emergency, crisis and austerity, the commodification of life, and the liberalization of trade.
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; discipline; genre; identités LGBTQIA2+; politique; périodes historiques; ressource en ligne; sciences de la gestion; sciences humaines; sociologie; thématiques; économie; égalité des sexes

Homophobia, conversion therapy, and care models for trans youth: Defending the gender affirmative approach - Ashley, Florence (Journal of LGBT Youth, 2019)
In recent years, opponents of the gender-affirmative approach to trans youth have argued that it bears homophobic roots and may be tantamount to conversion therapy. This argument is mistaken. In this article, I first argue that there is no evidence that social and/or medical transition is motivated by homophobia. Contrary to the critique’s tacit premise, many if not most trans people are LGBQ following transition. Furthermore, despite social progress in the last decade, transphobia remains more common than homophobia. Second, the gender-affirmative approach is fundamentally dissimilar to conversion therapy, unlike clinical approaches that oppose affirmation and seek to prevent transition. The comparison to conversion therapy relies on a superficial understanding of sexual orientation, such that a change of label (e.g. straight, bisexual, gay, lesbian) is equivalent to a change of sexual orientation even without changes to the targets of sexual attraction. By contextualizing conversion therapy in relation to trans youth care, I show that, on the contrary, conversion therapy has long focused on preventing transgender youth from growing up trans.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; cours; fem1000; identités LGBTQIA2+; militance; personnes trans*; premier cycle; périodes historiques; thématiques

Articulation des questions trans en travail social : pratiques et points de vue des intervenant.e.s sociaux - Faddoul, Maxime (Université du Québec à Montréal, 2019)
Partant du point de vue trans de l'auteur, plusieurs constats s'imposent à l'égard des questions trans en travail social. Premièrement, la recherche et la pratique en travail social ont joué un rôle historique dans l'encadrement et le contrôle des parcours de transition. Deuxièmement, il y a une rareté de contenu sur les questions trans dans la formation en travail social. Conséquemment, les travailleur.se.s sociaux ne sont pas formé.e.s pour intervenir avec les personnes trans. La question ayant guidé cette recherche est la suivante : quelles sont les pratiques d'intervention sociale mises en œuvre auprès des personnes trans dans les milieux institutionnels, communautaires et privés à Montréal, et comment celles-ci répondent ou non aux besoins des personnes trans? Mes objectifs de recherche sont multiples : 1) recenser les lieux où les praticien.ne.s du travail social sont amené.e.s à travailler avec des personnes trans; 2) analyser les discours qui sous-tendent les pratiques d'intervention et les comparer selon les contextes organisationnels; 3) identifier les barrières et leviers pour l'intervention trans-affirmative. La méthodologie de recherche est féministe et qualitative. Neuf entrevues semi-dirigées ont été réalisées avec des intervenant.e.s sociaux travaillant avec des personnes trans. Cette recherche démontre qu'en dépit des différents contextes organisationnels, plusieurs barrières et leviers pour l'intervention avec les personnes trans sont similaires. L'analyse et la discussion ont été menées à l'aide d'un cadre conceptuel arrimant des concepts en études trans comme le cisgenrisme, la cisnormativité et la transmisogynie avec la conceptualisation de la pratique du travail social de Karen Healy sur les contextes organisationnels et les discours y circulant. L'analyse se concentre, premièrement, sur les discours en place dans les contextes organisationnels, soit la pathologisation de la transitude, la cisnormativité et les interventions trans-affirmatives. Deuxièmement, l'imprévisibilité des services octroyés aux personnes trans est discutée, notamment que cette imprévisibilité résulte des limites des connaissances et des compréhensions de la transitude chez les intervenant.e.s sociaux. Troisièmement, je présente des stratégies pour lutter contre la cisnormativité en intervention, soit la posture de l'intervenant.e, ses connaissances et son engagement social et politique. En conclusion, je résume les faits saillants de cette étude et évoque ses apports théoriques et pratiques. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : cisgenrisme, cisnormativité, contextes organisationnels, pratiques trans-affirmatives, théorie trans, transféminisme, travail social
Keywords: 2000 à aujourd'hui; 2010-2019; IREF; amériques; discipline; identités LGBTQIA2+; mémoires/thèses; personnes trans*; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail social

Corps et résistances - Institut de recherches et d'études féministes (FéminÉtudes, 2019)
FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Un zine en format papier accompagne le numéro.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; corps; féminétudes; genre; identités LGBTQIA2+; intersectionnalité; militance; personnes trans*; périodes historiques; queer; québec; régions géographiques; thématiques; écriture des femmes*

Un appartement sur Uranus : chroniques de la traversée - Preciado, Paul B. (Grasset, 2019)
« Je ne suis pas un homme je ne suis pas une femme je ne suis pas hétérosexuel je ne suis pas homosexuel je ne suis pas bisexuel. Je suis un dissident du système genre-genre. Je suis la multiplicité du cosmos enfermée dans un régime politique et épistémologique binaire, et je crie devant vous. Je suis un uraniste confiné dans les limites du capitalisme technoscientifique." Paul B. Preciado écrit entre les possibles - et faisant ce qu'il déploie un autre possible. Il fait la politique avec un enthousiasme contagieux, sans aucune hostilité. Ce livre est l'histoire de ses transitions. Cette histoire n'est pas celle du passage d'un point à un autre, mais de l'errance et de l'entre-deux comme lieu de vie. Une transformation constante, sans identité fixe, sans activité fixe, ni adresse, ni pays : les transitions sont sa maison. Et cette maison, vous lecteur, si vous y entrez, vous ne voudrez plus jamais la quitter tout à fait, jamais oublier sa langue intermédiaire, sa langue carrefour, sa langue en transition." Virginie Despentes »
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; approches et analyses; com5170; cours; europe; fem1000; fem3200; france; har4600; identités LGBTQIA2+; personnes trans*; premier cycle; périodes historiques; queer; régions géographiques; thématiques

Introduction : Un appartement sur Uranus et Lettre d’un homme trans à l’ancien régime sexuel dans Un appartement sur Uranus: chroniques de la traversée - Preciado, Paul B.; Despentes, Virginie (Un appartement sur Uranus: chroniques de la traversée, 2019)
Je ne suis pas un homme je ne suis pas une femme je ne suis pas hétérosexuel je ne suis pas homosexuel je ne suis pas bisexuel. Je suis un dissident du système sexe-genre. Je suis la multiplicité du cosmos enfermée dans un régime politique et épistémologique binaire...Je n'apporte aucune nouvelle des marges. Je vous offre un morceau d'horizon.
Section: 1 vol. (293 p.) ; 18 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexualité; soc3113; sociologie; systèmes d'oppressions; thématiques

“Saw you in the dark”: Exploring Rufus Wainwright’s emotional vulnerability in fan-captured live performance videos - Salerno, Stephanie (Performance Matters, 2019)
A Victorian-inspired, deplumed, black mourning gown; a video of a kohl-painted eye, staring, blinking, and weeping; and a baritone voice mingling with solo piano are the audio and visual touchstones of Rufus Wainwright’s 2010 live tour of All Days Are Nights: Songs for Lulu. Using performance analysis of fan-captured performances posted on YouTube, this article argues that digital viewership queers, or alters, the audience’s experience, thus empowering spectators to engage with the emotional vulnerability, grief, and genre-bending of Lulu. For a work like Lulu, performed as a song cycle and without official music videos or a professional live recording, fan videos fill a void, at once cutting a major expense of the artist/label while empowering the audience to capture and share what they find to be meaningful online. In this study, four fan-captured live Lulu performances reveal moments of elision, uncertainty, and the blurring of the artist and the artist’s persona within digital “third space.” Through this lens, persona and grief are read within digital viewings of Wainwright’s live performances while framing online spectatorship as a queer practice of meaning-making.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amériques; approches et analyses; culture populaire; deuil; identités LGBTQIA2+; masculinité; médias sociaux; new york; périodes historiques; queer; représentations médiatiques; ressource en ligne; régions géographiques; sofia; stéréotypes de genre; thématiques

Structural competency in emergency medicine services for transgender and gender non-conforming patients - Willging, Cathleen; Gunderson, Lara; Shattuck, Daniel; Sturm, Robert; Lawyer, Adrien; Crandall, Cameron (Social Science & Medicine, 2019)
In this formative qualitative research, we draw upon the concepts of structural vulnerability and structural competency to examine how transgender and gender non-conforming (TGGNC) patients and healthcare personnel experience service delivery in Emergency Departments (EDs), and how this experience can be improved upon. Between October 2016 and June 2017, we undertook 31 semi-structured interviews with TGGNC patients (n = 11) and physicians (n = 6), nurses (n = 7), and non-clinical staff (n = 7) in four community-based EDs in New Mexico. Our iterative coding and analysis process resulted in eight sets of findings: (1) reasons why TGGNC patients seek care from EDs; (2) perceptions about and experiences of TGGNC patients; (3) relevance of gender identity and sex at birth; (4) bureaucracy and communication; (5) spatial considerations; (6) preparing providers and staff to care for TGGNC patients; (7) the lack of resources for structural prescriptions; and (8) respect, humanity, and sameness. Findings suggest that structural issues adversely impact the health and wellbeing of TGGNC patients and service-delivery practices in the ED. We describe study implications for training ED personnel and modifying this practice setting to prevent delayed care and ensure appropriate services for TGGNC patients in need of structurally competent emergency medicine.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amériques; anthropologie; discipline; personnes trans*; projet charge mentale; périodes historiques; régions géographiques; santé; sciences humaines; service d'urgences; thématiques; états-unis

Trans self-identification and the language of neoliberal selfhood: Agency, power, and the limits of monologic discourse - Zimman, Lal (International Journal of the Sociology of Language, 2019)
Sociocultural linguists share with transgender communities a strong interest in the power of individuals to assert agency over linguistic patterns. For trans people, a key principle of activism is gender self-determination, which treats each individual as the ultimate authority on their own gender identity. This article explores some of the ways gender self-determination and self-identification surface in transgender people’s linguistic practices. Three particular manifestations are highlighted: gendered identity labels, third person pronouns, and body part terminology. The observations offered on these subjects are based on a series of ethnographic projects carried out from 2006–2016 in transgender communities across several metropolitan areas in the United States and in online spaces frequented by trans people. However, the analysis goes beyond mere description by treating this kind of individualized linguistic agency as the product of cultural practice rather than an asocial given. Such a perspective introduces questions concerning why this form of agency arose in the time and place that it has. This article frames gender self-identification as an enactment of neoliberal personhood, in which individuals are framed as the driver of their destiny. What the ideology of neoliberal agency obscures, however, is that agency is not an equally distributed resource.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; agentivité; amériques; approches et analyses; cours; discipline; identités LGBTQIA2+; lin2685; linguistique; néolibéralisme; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sofia; thématiques; transféminisme; états-unis